Preparation of Nano-Strontium Titanate Based on Glass Fiber Filter and Its Application in Speciation Analysis for Chromium - Zhang, Dong; Jie Sun, Ya (Asian Journal of Chemistry, 2013)
Nano-strontium titanate based on glass fiber filter was successfully prepared by sol-gel method and characterized using XRD and SEM. Its application in speciation of Cr(III) and Cr(VI) from water was studied. Adsorption and elution were investigated under different conditions. The results showed that the nano-strontium titanate could crystal based on glass fiber, gaining a new block adsorbent like a leaf. At normal temperature, the adsorbent had strong adsorption capacity for Cr(III) and Cr(VI) in water, but two forms of chromium show different adsorption capacities at different pH values, that is, Cr (III) selectively retained at pH 7-14, but Cr(VI) can't be adsorbed. Whereas Cr(VI) retained at pH 1-3, but Cr(III) can't be adsorbed. Hence complete separation of the two forms of chromium is possible. Retained Cr(III) and Cr(VI) were eluted with 1 mol/L HCl and 2 mol/L NaOH, respectively. Based on these, a simple and sensitive method for the speciation, separation and preconcentration of Cr(VI) and Cr(III) in environmental water was developed. The method was applied for the speciation of chromium in environmental water samples and measured by atomic absorption spectroscopy.